PENINGKATAN KEMAMPUAN SISWA TERHADAP TEKS WACANA DENGAN MODEL PEMBELAJARAN KOOPERATIF SCRIPT DI KELAS X MERDEKA SMA NEGERI 14 JENEPONTO - Marhani Marhani; Sitti Rabiah; Nurfathana Mazhud (JURNAL NALAR PENDIDIKAN, 2023)
This study aims to describe the improvement of students' ability to exposition discourse texts using a script cooperative learning model in grade X Merdeka A UPT SMA Negeri 14 Jeneponto students. This research is a type of classroom action research that has four stages including: planning, implementation, observation and reflection. The results of this study are based on observations made in the precycle, cycle I to cycle II the attitudes shown by students from the activities carried out show different attitudes. The results of observations in cycle I showed a percentage of 79.3% while in cycle II it was seen that students became more active and enthusiastic in learning. This is also based on the results of cycle II observations which show a percentage of 90.6%. Student responses from cycle I to cycle II actions have increased very significantly. The results of student test scores during precycle activities of students who achieved KKTP were 4 people or 11.76%, in cycle I activities students who reached KKTP as many as 12 people or 0.37% and in cycle II activities students who achieved KKTP as many as 32 people or 100%. Therefore, it can be concluded that the script cooperative learning model is stated to be able to improve students' ability to discourse texts.